Increased Vitamin B12 Levels in Patients with Oral Cancer - Prashant Gupta; Subhash Chandra; Awanindra Kumar Jha; Tanya Khaitan; Anjani Kumar Shukla; Shantala R Naik (Indian Journal of Dental Research)
Background: Oral cancer (OC), which happens to be one of the leading causes of death in the Indian population, is caused primarily by tobacco use, although other factors are also responsible. Serum vitamin B12 is important in maintaining the immune system and also repairing the damaged deoxyribonucleic acid (DNA) of cells. The aim of our study was to evaluate the serum B12 levels in patients with OC and look for any association between the two. Methods: One hundred subjects were selected for the study and divided into two groups: group A having OC (including cases of oral squamous cell carcinoma (OSCC), verrucous carcinoma and oropharyngeal carcinoma; 50 patients) and group B had age- and gender-matched healthy controls (50 healthy volunteers). Patients diagnosed clinically and histopathologically confirmed as OC were selected for the study. All the patients were subjected to haematological investigation to assess serum vitamin B12. Results: Males subjects in the 4th and 5th decades of life were predominantly affected. Serum vitamin B12 was significantly increased in OC patients when compared with controls, which was statistically significant. The mean serum vitamin B12 was slightly higher in males than in females, which was statistically non-significant. Conclusion: Our study found increased vitamin B12 levels in OC patients, and it was statistically significant.